Evaluating organic matter removal efficiency in pig farm wastewater after biogas tank using a two-stage filtration system with biochar from Mimosa pigra - Nguyễn, Thị Phượng; Nguyễn, Xuân Cường; Trần, Thị Cúc Phương; Nguyễn, Thị Hoài Giang; Nguyễn , Thị Thảo Nguyên (Hue University Journal of Science: Natural Science, 2025)
This study uses biochar from Mimosa pigra plants as the filter material for a two-stage anaerobic-aerobic filtration system, aiming to evaluate the organic matter removal efficiency in pig farm wastewater after passing through a biogas tank. Two identical experimental systems, A and B, were designed, each consisting of an anaerobic filter column and an aerobic filter tank. System A operated with an organic loading rate (OLR) ranging from 71.11 to 243.75 g COD/m³/day and a hydraulic loading rate (HLR) ranging from 74.94 to 112.41 L/m²/day, while system B operated with an OLR from 103.26 to 493.01 g COD/m³/day and an HLR from 37.47 to 112.41 L/m²/day. The results show that both systems achieved a high COD (chemical oxygen demand) removal efficiency, with system B averaging 87 ± 4%, higher than system A (86 ± 3%), despite system B's higher OLR. Balancing HLR and OLR, depending on the actual conditions of the filter tank, influent loading, and treatment requirements, is crucial for optimizing the treatment efficiency and ensuring the economic viability.